Sex-specific differences and risk factors for 30-day mortality in acute pulmonary embolism – results from the Serbian University Multicenter Pulmonary Embolism registry - Matijašević, Jovan; Mirić, Milica; Vučićević Trobok, Jadranka; Peković, Sandra; Andrijević, Ilija; Džudović, Boris; Subotić, Bojana; Obradović, Slobodan (Vojnosanitetski pregled, 2022)
Background/Aim. The prediction role of gender in early mortality in patients with acute pulmonary embolism (PE) is still debatable. The aim of the study was to examine sex-specific factors in all-cause 30-day mortality in patients suffering from acute PE. Methods. Acute PE subjects (n = 532), 49.6% men, were derived from a “real-life” observational multicenter study. We assessed independent risk factors as predictors for early (one-month) fatal outcome in men, women and total population using univariate Cox regression analysis. Results. Age, obesity, hypertension, renal dysfunction, anemia, community-acquired pneumonia, and smoking history presented statistically significant sex-specific differences. One-month mortality was 13.7%, without significant difference in survival based on sex (Log Rank test; p = 0.324). Tachycardia at admission [hazard ratio (HR) = 2.61, p = 0.004], coronary artery disease (HR = 2.30, p = 0.047), immobilization four weeks prior to a PE episode (HR = 2.31, p = 0.018) and older age (HR = 1.03, p = 0.017) in women, while chronic obstructive pulmonary disease (COPD) (HR = 4.03, p < 0.001) and leukocytosis (HR = 1.19, p < 0.001) in men significantly increased one-month mortality risk. Conclusion. Patient’s sex did not prove to be the independent predictor for 30-day mortality in PE patients. We found that tachycardia at admission, older age, coronary artery disease and limb immobilization four weeks prior to PE in women, whereas COPD and elevated leukocyte count in men were associated with higher chance of all-cause early mortality.